2022
DOI: 10.56499/jppres22.1378_10.4.737
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Aloe vera on fasting blood glucose levels in pre-diabetes and type 2 diabetes mellitus: A systematic review and meta-analysis

Abstract: Context: Aloe vera is a traditional medicinal plant that shows a wide range of biological activities. Previous studies demonstrated the antihyperglycemic effect of Aloe vera but with inconsistent results. Aims: To quantitatively summarize the effect of Aloe vera on fasting blood glucose in pre-diabetes and type 2 diabetes mellitus by a meta-analysis. Methods: PubMed, Scopus, Springer Link, Science Direct, Proquest, and Google Scholar were used to identify clinical trials evaluating the effect of Aloe vera on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…An earlier meta-analysis study claimed that Aloe vera significantly lowered fasting blood glucose in the intervention group compared to controls (Budiastutik et al, 2022). Some studies use Aloe vera in capsules, gels, and juice (Soni et al, 2014;Surya et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…An earlier meta-analysis study claimed that Aloe vera significantly lowered fasting blood glucose in the intervention group compared to controls (Budiastutik et al, 2022). Some studies use Aloe vera in capsules, gels, and juice (Soni et al, 2014;Surya et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Patients have used it for a long time to help lower plasma glucose concentration in people with diabetes or prediabetes. Some substances found in Aloe vera called chromium and alprogen can help fix damaged insulin cells in the pancreas, improve the working of insulin, and reduce high blood sugar levels [31].…”
Section: Aloe Veramentioning
confidence: 99%
“…A systematic review and meta-analysis was published in 2022 and included 642 patients, and found reduced FPC in patients with prediabetes and T2D. However, the sample size of the clinical trials was small in size, and most of the studies' periods were short [31]. The previous clinical studies did not notice any negative herb-drug interaction [25].…”
Section: Aloe Veramentioning
confidence: 99%
“…These components contribute to its potent antidiabetic and anti-inflammatory properties ( 30 , 31 ). Furthermore, aloe vera is an effective agent in combating most diseases ( 32 ) and can decrease blood glucose in diabetic patients ( 33 ). There are many vitamins, minerals, and antioxidants in aloe vera gel ( 34 ), which is used to enhance the nutritional quality of some juices and can be consumed because of its beneficial influence on health ( 35 ).…”
Section: Introductionmentioning
confidence: 99%